Deformation analysis of a geodetic monitoring network - Setan, Halim; Singh, Ranjit (Geomatica, 2001)

(untitled)
Results of deformation analysis are directly relevant to the safety of human life. Therefore one has to be very careful in assessing the data of a monitoring network to avoid wrong interpretation of the displacements. This paper presents a deformation analysis procedure that consists of network adjustment of individual epochs, trend analysis of the displacement field and modelling of the deformation. During trend analysis, two robust methods and a non-robust method have been adopted and applied in determining the trend of movements for all the common points in a monitoring network. The trend of movements then form a basis for preliminary identification of the deformation models. The developed procedure has been implemented in a program package known as NETDEFAN (NETwork and DEFormation ANalysis). A numerical example is also given by using known data of a dam monitoring network.